LOMS.cz computational platform for high-throughput classical and combinatorial Judd-Ofelt analysis and rare-earth spectroscopy - Jan Hrabovsky; Petr Varak; Robin Krystufek (Scientific Reports)
Abstract We present LOMS.cz (Luminescence, Optical and Magneto-optical Software), an open-source computational platform that addresses the long-standing challenge of standardizing Judd-Ofelt (JO) calculations in rare-earth spectroscopy. Despite JO theory’s six-decade history as the fundamental framework for understanding $$4f\leftrightarrow 4f$$ transitions, the field lacks standardized computational methodologies for precise and reproducible parameter determination. LOMS integrates three key innovations: (1) automated computation of JO parameters, transition probabilities, branching ratios, and theoretical radiative lifetimes, (2) a dynamically expanding database of experimentally validated parameters enabling direct comparison between computed and empirical results, and (3) a novel Combinatorial JO (C-JO) analysis algorithm that systematically identifies optimal absorption band combinations to ensure reliable parameter extraction. As a proof-of-concept, we demonstrate how this computational framework enables rapid screening of spectroscopic parameters, allowing researchers to predict optical properties with enhanced reliability. By combining automated analysis with experimental validation through its integrated database, LOMS.cz establishes a standardized platform for accelerating the discovery and optimization of rare-earth-based photonic and optoelectronic materials.